Molecular basis and rationale for combining immune checkpoint inhibitors with chemotherapy in non-small cell lung cancer. (September 2019) - Leonetti, Alessandro; Wever, Birgit; Mazzaschi, Giulia; Assaraf, Yehuda G.; Rolfo, Christian; Quaini, Federico; Tiseo, Marcello; Giovannetti, Elisa
Abstract: Immunotherapy has prompted a paradigm shift in advanced non-small cell lung cancer (NSCLC) treatment, by demonstrating superior efficacy to chemotherapy alone both in second- and in first-line setting. Novel insights on molecular mechanisms and regimens to enhance the efficacy of immunotherapy are warranted, as only a minority of patients (˜20%) respond to checkpoint blockade. Taking into account the multiple mechanisms adopted by tumor cells to evade the immune system through cancer immunoediting, the frontline combination of immune checkpoint inhibitors with chemotherapy appears to be a successful strategy as: 1) it enhances the recognition and elimination of tumor cells by the host immune system (immunogenic cell-death), and 2) it reduces the immunosuppressive tumor microenvironment. Remarkably, the immune checkpoint inhibitors pembrolizumab and atezolizumab have already been approved by the FDA in combination with chemotherapy for the first-line treatment of advanced NSCLC and many other chemo-immunotherapeutic regimens have been evaluated as an initial therapeutic approach in metastatic NSCLC. Concurrently, several preclinical studies are evaluating the molecular mechanisms underlying immunomodulation by conventional chemotherapeutic agents (platinum salts, antimitotic agents, antimetabolites and anthracyclines), unraveling drug- and dose/schedule-dependent effects on the immune system that should be exploited to achieve synergistic clinical activity. The current review provides a detailed overview of the immunobiological rationale and molecular basis for combining immune checkpoint inhibitors with chemotherapy for the treatment of advanced NSCLC. Moreover, current evidence and future perspectives towards a better selection of patients who are more likely to benefit from chemo-immunotherapy combinations are discussed.